Self selection and post-entry effects of exports: Evidence from Italian manufacturing firms - Francesco Serti; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
Our paper adds empirical evidence on the causal effects of exporting on firms' performances. Using a rich database on Italian manufacturing firms, we test the self-selection and the post-entry effects hypotheses with respect to various firms' characteristics. Our analysis supports the idea that the superior performance of the exporters is due not only to a market selection mechanism, but also to efficiency improvements following the export activity. We find heterogeneous post entry effects with respect to characteristics as geographical location, size and sector. To test the post entry hypothesis we implement the propensity score matching and Differences in Differences techniques.
Keywords: D24; F14; O31; 330; Self selection; Post-entry effects; Export; Matching; Außenhandelssektor; Markteintritt; Produktivität; Industrie; Schätzung; Italien